Justification of recommendations for the introduction of active coal during the long-term storage of armored weapons - Kostiuchenko , Serhii; Hudyma , Viktor; Ostrovskyi , Anatolii; Novikova , Iryna (Social Development and Security, 2021)
The environment is a constant carrier of aggressive corrosive reagents. In general, it includes atmospheric air, which consists of nitrogen, oxygen, hydrogen, carbon dioxide and inert vapors, gases and solids (dust). Almost all components affect the course of corrosion processes. Details of modern machines are made mostly of an alloy of different metals. The use of alloys increases the strength of products, improves their wear and other properties. The main type of destruction of metal products is electrochemical corrosion. For its flow, an electrolyte is needed, which can be formed on the surface of the parts in the form of small drops of atmospheric moisture, as well as anode and cathode sections. Anode and cathode areas on the surface of parts appear not only due to the collision of different materials, but also not the same degree of surface treatment. Almost microgalvanic vapors occur wherever there are drops of moisture on the metal. The most effective protection of machines against corrosion is provided by the formation on the surface of mechanical barrier parts, but in armored vehicles, there are a number of parts that can not be covered with oil, and a number of systems (mainly electronic equipment and optical devices) are very sensitive to atmospheric and cannot be protected by oils. Therefore, found the so-called method of processing the environment. An example of such a method is the sealing of the tank and drying of the air inside with silica gel (SiO2 · 3H2O). Silica gel of MSC and KSM grades (lump and granular) is used to dry the air in the middle, which is a dried silicic acid gel.